Tensile Properties of Glass Fiber Reinforced Polyamide 6-Polypropylene Composites - Nurizzathanis, Mohamad Kusaseh; Dewan Muhammad, Nuruzzaman; Chowdhury, Mohammad Asaduzzaman; Oumer, A. N.; Noor Mazni, Ismail; Shahnor, Basri (2017)
In this research study, glass fiber (GF) reinforced polyamide 6 (PA6)-polypropylene blends were prepared using injection molding machine. Test specimens of five different compositions such as, 70%PA6+30%PP, 65%PA6+30%PP+5%GF, 60%PA6+30%PP+10%GF, 55%PA6+30%PP+15%GF and 50%PA6+30%PP+20%GF were prepared successfully. The effects of glass fiber content on the tensile properties of the composites were investigated. Test results reveal that yield strength, elastic modulus, tensile strength and tensile elongation are influenced by glass fiber content. Results show that yield strength is low for 70%PA6+30%PP pure polymer blend whereas 50%PA6+30%PP+20%GF composite shows high yield strength. Test results also show that elastic modulus is low for 70%PA6+30%PP, it increases with the increase in fiber content and elastic modulus is remarkably high for 50%PA6+30%PP+20%GF composite. On the other hand, tensile strength is low for 70%PA6+30%PP blend and tensile strength of GF reinforced composite increases steadily with the increase in glass fiber content. In addition, the tensile elongation of 70%PA6+30%PP pure blend is very high, whereas the composite shows reduced tensile elongation with the increase in fiber content and particularly, 50%PA6+30%PP+20%GF composite shows notably low tensile elongation.